FAKTOR PENYEBAB KESULITAN MEMBACA DAN STRATEGI GURU DALAM MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS II SD 3 GULANG - Elisa Septiana; Lia Fatmawati; Rani Setiawaty (Jurnal Lensa Pendas, 2024)
This research was motivated by several students in class II of SD 3 Gulang who were still experiencing difficulties in their reading skills. So an in-depth analysis is needed to be able to find out the factors causing students who still have difficulty in their reading skills. The method used in this research is a qualitative descriptive research method with a case study approach. Data were collected through observations, documentation and interviews conducted with the homeroom teacher for class II at SD 3 Gulang. The results of the research show that there are still several class II students at SD 3 Gulang who still have difficulty in their reading skills because they are influenced by several internal and external factors. Internal factors originating from the students themselves include lack of motivation to learn, low memory, and difficulty in distinguishing letters that look the same. Meanwhile, external factors include a student learning environment that is less supportive, parents who lack attention to their children's learning development, and inadequate facilities and infrastructure which cause students to experience limitations in learning. The strategy used by teachers to overcome this problem is by (1) providing guidance to students, (2) providing attention and motivation to students, (3) applying learning media in the form of letter cards, (4) applying the dictation method, and (5) increase class hours to practice reading.